Islamic economic thought in Malaysia (1900-1980) : ideas, setting, interaction - Fauwaz bin Abdul Aziz (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2013)
This study surveyed a range of ideas of a select group of Malaysia's ulama and religious intellectuals who contributed to the discussion of economic matters from the early 1900s to the early 1980s. These ideas were then placed in context–including the political and social–to show the interaction between those of 'economic' concern and the circumstances that served as their setting. The work focused on three of the most representative scholars, Daud Abdullah al-Fatani, Muhammad Ismail al-Fatani and Zayn al-'Abidin al-Fatani, of the Malay traditional jurisprudence of the 19th century relating to economic subjects, moved to the economic ideas of the religious reformists of the early to mid-20th century, such as Syed Sheikh Ahmad Hasan al-Hady, Salimin Nu'man, Abu Bakar Ash'ari and Zainal Abidin Ahmad, then examined the Islamic 'political economy' of the late 1940s and early 1950s, in the ideas of Abu Bakar al-Bakir, Burhanuddin al Helmy, Dhulkifli Muhammad and Baharuddin Abdul Latif. The economic ideas of the 'da'wah' movement of the 1960s and 1970s, namely those of Anwar Ibrahim, Siddiq Fadhil and Ashaari Muhammad, were then examined, followed by a summary treatment of the ideas current in the 'Islamisation' of economic activities of the 1980s, including those of Mahathir Mohamad, Aidit Ghazali and Muhammad Syukri Salleh. It was found that throughout the various stages of Islamic economics, their development lacked those characteristics needed to make up a conceptual and operational framework for it. In the early phase, the ideas lacked a methodology to dynamically relate the traditionalist text-based jurisprudence to the socio-economic and political circumstances of the times. The ideas of the 1940s and 1950s held the most potential in terms of formulating a comprehensive framework for Islamic economic ideas, but that potential was not realised due to the focus on the pressing political questions of the day. The study also revealed that the most recent stage of Islamic economic ideas in Malaysia, the norms, practices and values, particularly in the Islamic banking and finance sector–has not maintained the connection with the traditional religious socio-cultural framework. The thesis joins those calling for Islamic economics to 'return' to the religio-socio-cultural framework, while at the same time addressing the 'political economic' challenges of the times as opposed to the merely 'technical' differentiation between Islamic economics and conventional economics, finance and banking.